Single-incision laparoscopic cholecystectomy: Feasibility and outcome - Abhishek Kumar Yadav,; Albail Singh Yadav,; Rahul Litoria,; Nalin Kumar Srivastava, (Asian Journal of Medical Sciences, 2025)
Background: Single-incision laparoscopic cholecystectomy (SILC) represents a minimally invasive surgical technique aimed at enhancing patient outcomes by reducing incisions. This study assesses the feasibility and clinical outcomes of SILC in comparison to conventional laparoscopic cholecystectomy. Aims and Objectives: The aims and objectives of the study are to evaluate the feasibility, operative outcomes, and patient satisfaction of SILC. Materials and Methods: A prospective observational study was conducted at Maharani Laxmi Bai Medical College, Jhansi from May 2023 to June 2024, including 50 patients undergoing SILC. Parameters such as operative time, intraoperative, and post-operative complications; pain scores; hospital stay; and cosmetic outcomes were analyzed. Results: The mean operative time was 46.60±5.986 min. Intraoperative complications were minimal, with a 2% incidence of adhesion and bleeding. Post-operative pain was significantly reduced, with mean Visual Analog Scale scores of 2.64±0.563 on day 1 and 1.52±0.544 on day 2. The average hospital stay was 2.90±0.416 days, and cosmetic satisfaction was high, with a mean score of 7.74±0.853. Conclusion: SILC is a feasible and effective alternative to multi-port laparoscopic cholecystectomy, offering reduced post-operative pain, shorter hospital stays, and improved cosmetic outcomes. Adequate training is essential to mastering the technique. Further studies of larger sample sizes are recommended.